MapSite - an Internet map service of the National Land Survey of Finland gets dressed up with modern technology - Rajalin, Jere (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
MapSite of the National Land Survey of Finland was the first national Internet map service in Europe. It was launched in September 1996. Since then the service has been a huge success. Until now it has almost 300,000 users in all, the number of paying customers is over 2,000. In the spring of 2001 National Land Survey (NLS) started a project to produce a new Internet map service to replace the old MapSite. The developing project is divided in three phases. In the first phase services of paying customers are renewed. Free of charge map browsing service is being modernised in the second phase. Totally new services may be produced in the third phase.